Efektivitas Layanan Aduan Lapor Bupati Berbasis E-Government di Kabupaten Pekalongan - Agung Barok Pratama; Arina Manasikana; Nurul Auliya Fadzlina (Univiversitas Dr. Djar Wattiheluw, 2023)
The public service sector is a reflection of the governance of a government. Poor public service delivery will certainly disrupt the stability of government administration because it will affect the level of public trust in the government. For this reason, the Pekalongan Regency Government created an e- government-based 'report the district head' complaint system as an effort to improve the quality of public services. This study aims to evaluate the implementation of the e- government based 'report the bupati' public complaint service in Pekalongan Regency and analyze the faktors of its application. The primary data source came from DINKOMINFO Pekalongan Regency and was analyzed descriptively qualitatively. The results of the study showed that the e-government-based regent complaint service implementation in Pekalongan Regency was not effective, the availability of resources was still minimal, socialization activities were inconsistent and uneven due to budget constraints. The faktors that influence its implementation are limited budget, human resources, infrastructure and supporting infrastructure.